Corporate Information Disclosure and Stock Market Valuation? A Dummy Variable Regresssion Approach - Ekene , Etoama Peter; Ebere , C.C. (Research Parks Publishers, 2023)
This work examined the link between corporate information disclosure and the stock valuation in Nigeria using a dummy variable regression approach. It specifically looked into the relationship between quality of information disclosure, timely disclosure of information, mode of accounting and all share index. The secondary data for the variables were sourced from Nigeria Stock Exchange report for the period of 15 years (2005-2019). The dummy regression analysis was used with the aid of the E-view statistical software to test the stated hypotheses for the above variables at 0.5 significant level. The result showed that there is a significant relationship between quality of information, timely disclosure of information, mode of accounting and all share index of the Nigeria stock market. On the aggregate, corporate information disclosure has a significant influence on stock market valuation in the Nigerian stock market. The study therefore recommended that corporate firms in Nigeria should abide by information disclosure policy so as the boost the awareness and confidence of the investors in the stock market.